My week with Marilyn [videorecording (DVD)] - Curtis, Simon, 1960-; Williams, Michelle, 1980-; Redmayne, Eddie, 1982-; Branagh, Kenneth; Jackson, Philip, 1948-; Jacobi, Derek; Jones, Toby, 1966-; Kitchen, Michael, 1948-; Dench, Judi, 1934-; Watson, Emma, 1990-; Ormond, Julia; Beale, Simon Russell; et al.
In the summer of 1956, 23-year-old Colin Clark, determined to make his way in the film business, worked as a lowly assistant on the set of The Prince and the Showgirl, the film that famously united Sir Laurence Olivier and Marilyn Monroe. When his diary account was published, one week was missing. This is the story of that week: an idyll in which he escorted a Monroe desperate to get away from Hollywood hangers-on and the pressures of work.